Engineering C–C Bond Cleavage Activity into a P450 Monooxygenase Enzyme - Miller, Justin C.; Lee, Joel H. Z.; Mclean, Mark A.; Chao, Rebecca R.; Stone, Isobella S. J.; Pukala, Tara L.; Bruning, John B.; De Voss, James J.; Schuler, Mary A.; Sligar, Stephen G.; Bell, Stephen G. (Journal of the American Chemical Society, 2023)
The cytochrome P450 (CYP) superfamily of heme monooxygenases has demonstrated ability to facilitate hydroxylation, desaturation, sulfoxidation, epoxidation, heteroatom dealkylation, and carbon–carbon bond formation and cleavage (lyase) reactions. Seeking to study the carbon–carbon cleavage reaction of α-hydroxy ketones in mechanistic detail using a microbial P450, we synthesized α-hydroxy ketone probes based on the physiological substrate for a well-characterized benzoic acid metabolizing P450, CYP199A4. After observing low activity with wild-type CYP199A4, subsequent assays with an F182L mutant demonstrated enzyme-dependent C–C bond cleavage toward one of the α-hydroxy ketones. This C–C cleavage reaction was subject to an inverse kinetic solvent isotope effect analogous to that observed in the lyase activity of the human P450 CYP17A1, suggesting the involvement of a species earlier than Compound I in the catalytic cycle. Co-crystallization of F182L-CYP199A4 with this α-hydroxy ketone showed that the substrate bound in the active site with a preference for the (S)-enantiomer in a position which could mimic the topology of the lyase reaction in CYP17A1. Molecular dynamics simulations with an oxy-ferrous model of CYP199A4 revealed a displacement of the substrate to allow for oxygen binding and the formation of the lyase transition state proposed for CYP17A1. This demonstration that a correctly positioned α-hydroxy ketone substrate can realize lyase activity with an unusual inverse solvent isotope effect in an engineered microbial system opens the door for further detailed biophysical and structural characterization of CYP catalytic intermediates.